Evaluation of Refresher Training Programme on Conservation Agriculture Practices - Sharma, B. C.; Kumar, Rakesh; Slathia, P. S.; Puniya, Ramphool; Vaid, Amrish (Indian Journal of Extension Education, 2021)
Human behavior consists of knowledge, skill and attitude and timely up gradation of these three components is must for better human resource development. Training is medium for modification of human behavior to efficiently discharge one’s own duties and responsibilities at their respective work place. The paper attempts to evaluate the impact of 10 days training programme entitled “Conservation agriculture practices for enhancing productivity and resource use efficiency in major cropping pattern” conducted in the Division of Agronomy, SKUAST-Jammu on knowledge of the participants regarding different aspects of conservation agriculture as well as their opinion towards overall organization of training programme. Gain in knowledge was taken as indicator for assessing the immediate output of the training programme. Participants were exposed to pre and post knowledge test and the results of two sample paired t-test (p=.000) so applied revealed that there was significant gain in knowledge about different aspects of conservation agriculture after attending the training programme. Overall majority of the respondents were of opinion that training programme was well planned and very effective and they had learned different practical aspects of conservation agriculture.
Keywords: Evaluation; Training; Test; Knowledge; Conservation agriculture; Opinion